Optimizing Hybrid Electric Microcar Design: A Simulation-Based Approach to Fuel-Cell Powertrains Analysis - Bartolucci, Lorenzo; Cennamo, Edoardo; Cordiner, Stefano; Donnini, Marco; Mulone, Vincenzo (Journal of physics. Conference series, 2024)
The pressing need to reduce emissions and pollutants requires a significant diversification of mobility solutions and energy sources used to this aim. Light quadricycles with electric powertrains are increasingly recognized in research and industrial sectors as viable alternatives for achieving urban sustainable mobility solutions. Their lightweight design, compact dimensions, simplified prototyping and manufacturing processes, high efficiency, and lower emissions across the entire life cycle contribute to their growing importance. In line with this trend, integrating a hydrogen fuel cells stack with a battery pack is a promising powertrain solution, leveraging both technologies’ strengths. However, the design and development of such hybrid systems necessitate advanced methodologies that can address the problem of significant prototyping costs and time commitments while still ensuring optimal configurations. The availability of detailed simulation tools integrated with hardware components (vehicle simulation platforms) plays a crucial role in this endeavor, enabling insights on local phenomena which otherwise would be neglected, as such the purge phase, strongly impacting on the global consumption. These test platforms encompass all the main subsystems to account for all the vehicle demands while ensuring very good reliability for the predictions of performance and allowing the validation of the components. This enables the possibility of testing the vehicle under a wide set of operating conditions (e.g., weather conditions and driving cycles) within a simulated environment, thus reducing the costs related to the component sizing issues. In this context, the work presented in this paper, develops the fuel cell stack sizing analysis of a hybrid electric microcar, proposing a methodological approach for the powertrain design process. A detailed simulation platform is introduced for a hybrid electric microcar. The two energy sources, namely the Li-ion battery pack and the fuel cell stack, have been experimentally characterized and implemented into the model, also considering the experimental performances of the balance of plant elements as of the DC-DC converter. A linear scale-up method is implemented on the fuel cell stack to consider different configurations, and a deep analysis of the hydrogen consumption, comprising the scale-up of the purge phase, is presented, proposing two different approaches to the problem. From a technological standpoint, different results regarding the choice of fuel cell size have been found. As an example, the role of purging and its relationship with the size of the fuel cell stack may lead to a 14 % increase in the vehicle’s estimated range with respect to the baseline. Cost analyses are then needed to reach a trade-off between the costs and the technological standpoints.